2013
DOI: 10.1007/s11481-013-9448-6
|View full text |Cite
|
Sign up to set email alerts
|

The Different Clinical Effects of Anti-BLyS, Anti-APRIL and Anti-CD20 Antibodies Point at a Critical Pathogenic Role of γ-Herpesvirus Infected B Cells in the Marmoset EAE Model

Abstract: The robust and rapid clinical effect of depleting anti-CD20 monoclonal antibodies (mAb) in multiple sclerosis (MS) demonstrates a critical pathogenic contribution of B cells. The clinical effect of anti-CD20 mAb has been replicated in a relevant preclinical MS model, experimental autoimmune encephalomyelitis (EAE) in marmoset monkeys (Callithrix jacchus). By contrast, treatment with mAbs against two essential cytokines in B cell activation growth and survival, i.e. BlyS/BAFF and APRIL, was only partially effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…According to our recently reported observations, this may be the lymphocryptovirus (LCV)-infected B cell. We found that LCV + B cells were more profoundly depleted by anti-CD20 mAb than with anti-BLyS mAb or anti-APRIL mAb (42). LCVs are a family of g-herpesviruses that infect B cells.…”
Section: Discussionmentioning
confidence: 85%
“…According to our recently reported observations, this may be the lymphocryptovirus (LCV)-infected B cell. We found that LCV + B cells were more profoundly depleted by anti-CD20 mAb than with anti-BLyS mAb or anti-APRIL mAb (42). LCVs are a family of g-herpesviruses that infect B cells.…”
Section: Discussionmentioning
confidence: 85%
“…Under nonpathogenic conditions, B cells cannot exert this function in vivo. However, we (15,18) found that infusion of autologous LCV-infected B cells, prepulsed in vitro with MOG34-56, into healthy rhesus monkeys or marmosets elicited CD8 + T cell activation in vivo. Therefore, the hypothesis tested in the current study is that LCV infection of B cells leads to limited processing of the exogenous encephalitogenic peptide MOG34-56 in such a way that the MOG40-48 epitope remains available for loading on MHC-E molecules and presentation to core pathogenic CD8 + T cells in the primate EAE model.…”
mentioning
confidence: 85%
“…We observed that the opposite clinical effect in relapsingremitting MS of an anti-CD20 Ab (ofatumumab) and atacicept, a soluble antagonist of the B cell cytokines BAFF and APRIL (not effective), could be replicated in marmoset EAE (13,14). The paradoxical clinical effects could be correlated with differential depletion of CalHV3-infected B cells (15).…”
mentioning
confidence: 89%
“…A possible explanation was found in the marmoset EAE model. We observed that in monkeys treated with anti-CD20 mAb the copy number of CalHV3 DNA in lymph nodes and spleen was strongly reduced while the copy number was increased in monkeys treated with anti-BlyS or anti-APRIL mAb (Jagessar et al, 2013b). Our interpretation of this finding is that B cells immortalized by the EBV-related γ -herpesvirus CalHV3 may not need BAFF or APRIL for their survival and thus ignore inactivation of the cytokines, while they express CD20 and can thus still be depleted with anti-CD20 mAb.…”
Section: Treatments Targeting B Cellsmentioning
confidence: 82%